Constantinople as 'New Rome' - MELVILLE-JONES, John Richard (Byzantina Symmeikta, 2015)
<!--[if gte mso 9]> 0 0 1 242 1385 University of Western Australia 11 3 1624 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> In modern works it is often stated that Constantinople was called ‘New Rome’ (or ‘Second Rome’), with the implication that this was an official title. This incorrect statement is particularly common in works written by scholars whose first, and perhaps only, language is English (which is why a thorough English-language study of the question, with the relevant evidence translated into English and analysed rather than simply accepted, is needed). Some ancient authors (writing long after the foundation of the city) do in fact say or imply that Constantinople was formally named ‘New Rome’ or ‘Second Rome’, but this claim is, as Franz Dölger wrote a long time ago, ‘auf einer Fiktion beruht’. These expressions belong to laudatory rhetoric and elevated historical prose and poetry, and are never found in official documents or on the coinage. Also, who could believe that Constantine I would ever have allowed any name other than his to be the official name of his new city? The present study examines the relevant evidence in order to demonstrate that it is wrong to say that Constantine’s city was ever officially called anything other than ‘Constantinople’. On the other hand, it also shows that in an ecclesiastical context it has been correct to refer to ‘New Rome’, ever since the decision of the Oecumenical Council of A.D. 381, arranged by Theodosius I. The question has often been discussed in the past, but this study of the evidence reaches a firmer conclusion than most previous discussions, explains why an incorrect opinion has flourished, analyses the evidence more closely and presents it in English. <!--EndFragment-->